Applying learning analytics to program curriculum review. Issue 3 (29th March 2019) - Armatas, Christine; Spratt, Christine F.
Abstract : Purpose: The purpose of this paper is to describe examples of the application of learning analytics (LA), including the assessment of subject grades, identifying subjects that need revision, student satisfaction and cohort comparisons, to program curriculum review. Design/methodology/approach: Examples of analyses that address specific questions that a curriculum review wishes to address are provided, together with examples of visualizations from the analyses to aid interpretation. Findings: The results show that using LA as a part of curriculum review can provide insights not possible with the traditional curriculum review methods and can yield useful and actionable insights. Research limitations/implications: The work in this paper illustrates another important application for LA and demonstrates the value this approach has for informing curriculum enhancement at the program level. Practical implications: The analyses described provide insights not possible with traditional curriculum review methods. However, the challenge remains to develop analytic tools that can assist teachers to conduct LA independently. Originality/value: LA have been used to predict grades or identify at-risk students (Gaševic et al., 2016), but there is little research on its use for curriculum evaluation (Méndez et al., 2014). This paper addresses this gap and provides examples of its application in program curriculum review and the insights it can provide.